1991
DOI: 10.1139/y91-030
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism increases serotonin turnover and sympathetic activity in the adult rat

Abstract: Adult, male Sprague-Dawley rats underwent surgical thyroidectomy (Tx) or sham surgery. In all three experiments from which data are reported, a 3-week recovery period was allowed. In experiments I and II, baseline measurements of colonic temperature (Tc) and urinary norepinephrine excretion (NE) were obtained, and both variables were monitored daily for the duration of the studies. After baseline measurements, half of each surgical group was given either triiodothyronine (T3) or vehicle injections subcutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…In this report, 5-HT and 5-HIAA were both increased in the majority of regions measured. Con sistent with this finding, we recently reported that surgical thyroidectomy in adult rats led to increased turnover of 5-HT(5-HIAA/5-HT) in the brain stem and spinal cord, which was normalized with T3 replacement [14].…”
mentioning
confidence: 69%
“…In this report, 5-HT and 5-HIAA were both increased in the majority of regions measured. Con sistent with this finding, we recently reported that surgical thyroidectomy in adult rats led to increased turnover of 5-HT(5-HIAA/5-HT) in the brain stem and spinal cord, which was normalized with T3 replacement [14].…”
mentioning
confidence: 69%
“…53 observed an increase in the 5-HT precursor L-tryptophan (L-TP), and Heal and Smith 54 found an increase in both 5-HT and 5-HIAA in the midbrain after T 3 application in euthyroid animals. In contrast, Henley et al 42,45 examined animals after thyroidectomy, which resulted in an elevated serotonin turnover rate; in these animals, T 3 replacement resulted in a significant decrease in the 5-HIAA/5-HT ratio in the brainstem. In the two studies of thyroid replacement after thyroidectomy, T 3 replacement for longer than 3.5 days reduced the 5-HT turnover in caudal brainstem to completely normal values.…”
Section: Effects Of Thyroid Hormone Application On Brain Serotonin Symentioning
confidence: 99%
“…One early study measured brainstem 5-HT concentrations and did not find significant differences compared to euthyroid animals. 40 Later, using more sensitive assay techniques, five studies measured 5-HT and 5-HIAA concentration or the 5-HIAA/5-HT ratio as an indicator of the serotonin turnover and reported increased 5-HT metabolites in the brainstem [41][42][43][44][45] (notice: one study calculated the inverse ratio, 5-HT/5-HIAA 41 ). Reduced 5-HT concentrations in the cortex, 46,47 and reduced concentrations of the serotonin precursor 5-HTP were reported in the whole brain 48 of hypothyroid adult rats.…”
Section: Measurements Of 5-ht and Its Metabolites In Adult Hypothyroimentioning
confidence: 99%
“…Evidence for the interaction between serotonin (5-hydroxytryptamine, 5-HT) and thyroid hormones originates mostly from the experimentally induced hypothyroid state in animals [3]. Decreased 5-HT [7, 8] and increased 5-hydroxyinoleacetic acid [9] concentrations were observed in neonatal and adult hypothyroid rats, suggesting an increased 5-HT turnover [7, 10], while T 3 administration to hypothyroid animals normalized 5-HT turnover to normal values [10]. …”
Section: Introductionmentioning
confidence: 99%